Penggunaan Media Bahan Ajar Flipbook dalam Meningkatkan Pemahaman Belajar Siswa di SDN 153 Kota Pekanbaru - Pahruddin Harahap; Rahma Yuni; Syamsi Dhuha; Wismanto Wismanto; M. Ibnu Haikal (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The problem behind this research is that students do not understand the material in the student books used at school, students still do not understand the learning material and there is only one teaching material used by teachers and students, namely the Teacher's Book and the Student's Book. The aim of this research is to determine the use of Flipbook teaching material media in improving students' learning understanding at SDN 153 Pekanbaru City. This type of research is qualitative. The data collection techniques used were observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the research show that the use of flipbook teaching materials is effective in increasing students' learning understanding. This is proven based on the results of interviews conducted by researchers with students showing that there is an increase in students' learning understanding before using the media and after using the flipbook media.